As representações construídas pelos educadores acerca do discurso interdisciplinar presente na Rede Municipal de Ensino de São Paulo entre os anos de 2001 a 2016 - Tedeschi, Sandra Maria (2019)
The public educational policies of the city of São Paulo have guided interdisciplinarity as one of the possible actions to promote the reorientation of curricula in the network. The scope of this thesis is to identify the representations built by educators about the interdisciplinary discourse of officiality, produced between 2001 and 2016. This is a qualitative research with an interpretative nature that chooses data collection and analysis techniques resulting from semi-structured interviews, which aimed to shed light on the discourses of teachers and pedagogical coordinators who experienced the implementation of these programs. To interpret the dynamics of appropriation of the concept of interdisciplinarity, the representations (meanings and meanings) that teachers and pedagogical coordinators attribute to the term and the existing connections between the actions developed by them and their relationship with the interdisciplinary approach, we use the Theory of Social Representation (TRS). We conducted a literature review in the area of interdisciplinarity and the extract of 8 official documents of curricular public policies of the Municipality of São Paulo between 2001 and 2016. The results show that, although interdisciplinarity has gained materiality in official curriculum programs, in practice, what took place in the network was the creation of a fictional field of possibilities, given the theoretical, methodological and conceptual fragility that is evident in the discourses on interdisciplinarity